Effect of sealant on some finishing properties of commercial plywood / Shuhaili Johar, Shaikh Abdul Karim Yamani Zakaria and Norhafizah Rosman - Johar, Shuhaili; Zakaria, Shaikh Abdul Karim Yamani; Rosman, Norhafizah (2012)
Finishing is important to protect the surface and helps to enhance the attractiveness of the surface texture. These studies was obtained with 300mm x I00mm x 12mm of grade B plywood which used to evaluate the surface quality based on three type of sealer i.e Acid Catalyst (AC), Nitrocellulose (NC) and Polyurethane (PU) and finishing system (1) a sealer + a top coat, (2) two sealers + a top coat and (3) three sealers +a top coat. The coated plywood was assessing for surface roughness, surface hardness, adhesion and household test with accordance to the American Standard (ASTM). The results revealed that PU sealer gives good properties on adhesion, hardness and household reagent. While for surface roughness, AC gives better properties compared to other sealer. For finishing system, system 3 gives better properties on surface roughness, adhesion, hardness and household reagent. But for household and hardness properties, system 2 is enough to make the surface better.